2008
DOI: 10.1016/j.resuscitation.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Liquid ventilation with perfluorocarbons facilitates resumption of spontaneous circulation in a swine cardiac arrest model

Abstract: Background-Induced external hypothermia during ventricular fibrillation (VF) improves resuscitation outcomes. Our objectives were twofold (1) to determine if very rapid hypothermia could be achieved by intrapulmonary administration of cold perfluorocarbons, thereby using the lungs as a vehicle for targeted cardiopulmonary hypothermia, and (2) to determine if this improved resuscitation success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 23 publications
4
43
0
1
Order By: Relevance
“…Recently, it was also importantly demonstrated that intra-arrest hypothermia induced by liquid ventilation facilitates resumption of spontaneous circulation in a swine cardiac arrest model. 19,20 In conclusion, the present study demonstrates that rapid cooling induced by TLV affords cardioprotection against prolonged and severe ischemia in rabbits, even when started later than a low rate surface cooling. This result also supports the need for further investigations of TLV in the resuscitation setting.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, it was also importantly demonstrated that intra-arrest hypothermia induced by liquid ventilation facilitates resumption of spontaneous circulation in a swine cardiac arrest model. 19,20 In conclusion, the present study demonstrates that rapid cooling induced by TLV affords cardioprotection against prolonged and severe ischemia in rabbits, even when started later than a low rate surface cooling. This result also supports the need for further investigations of TLV in the resuscitation setting.…”
Section: Discussionsupporting
confidence: 53%
“…20 In large animals, hypothermic TLV was also reported to provide very fast cooling and to reduce the pulmonary artery temperature to 32°C within 9 to 10 minutes when instituted intra-arrest in a ventricular fibrillation model in swine. 22 Importantly, the rapid hypothermia elicited by TLV was associated with potent neurological protection and an increase in survival rate compared with control conditions. Animal studies have indicated that the neuroprotective effect of hypothermia is time dependent and that a large part of the protection is lost when cooling is delayed.…”
Section: Chenoune Et Al Liquid Ventilation Hypothermia and Cardiac mentioning
confidence: 97%
“…11,[17][18][19][20][21][22] These liquids can use the lungs as heat exchangers while maintaining normal gas exchanges. 18 -20 In addition, this ventilation procedure protects lung integrity.…”
Section: Clinical Perspective On P 911mentioning
confidence: 99%
See 1 more Smart Citation
“…Tierexperimentelle Daten weisen darauf hin, dass die Behandlungsergebnisse umso besser sind, je früher nach dem ROSC gekühlt wird [753]. Letztendlich könnte der Nutzen am größten sein, wenn bereits während des Kreislaufstillstands mit der Kühlung begonnen wird; Labordaten deuten darauf hin, dass dies den ROSC sogar erleichtert [754,755]. Verschiedene klinische Studien konnten zeigen, dass die Hypothermie präkli-nisch eingeleitet werden kann [511, 729,730,732,741], allerdings gibt es bis bisher keine klinischen Daten, die belegen, dass ein rasches Erreichen der Zieltemperatur zu einem besseren Outcome führt.…”
Section: Temperaturkontrolleunclassified